Stage II Keratoconjunctivitis in a goat: a case report - Abdullah, Faez Firdaus Jesse; Radzuan, Nurul Syazwani; Tijjani, Abdulnasir; Adamu, Lawan; Abba, Yusuf; Mohammed, Konto; Osman, Abdinasir Yusuf; Roslim, Noorashimah; Awang, Dayang Norhaizam; Saharee, Abdul Aziz; Saad, Mohd Zamri; Haron, Abdul Wahid (International Organization of Scientific Research, 2014)
A two year old Australian Feral male goat weighing 30 kg was presented to the large animal unit of Universiti Putra Malaysia Veterinary Hospital with the clinical signs of conjunctivitis and corneal ulceration with purulent ocular discharge. A sterile swab was taken from the eyefor bacteriological culture and the culture yielded a mixed growth of Pseudomonas aeroginosa and Moraxella caprae. The condition was diagnosed as pink eye disease. The goat was administered 3ml of 20mg/kgoxytetracyclinesubconjunctival injection of 0.4ml, intravenous injection of 2.2mg/kg Flunixin meglumine (antipyretic) agent, topical application of terramycine eye ointment and infusion of 2L of 0.6% Nacl solution. The signs of conjunctivitis and corneal ulcers of the eye had substantially reduced five days post treatment. Quarantine of infected animals, good quality feeding and fly control was recommended as preventive measures.